The Effect of the 5E Learning Model Supported with Material Ensuring Conceptual Change on Science Achievement: The Example of â€œHeat and Temperatureâ€ - IÅŸcan, YÄ±lmaz Vahit Vahit; Seyhan, Hatice GÃ¼ngÃ¶r (Universitas Pendidikan Indonesia, 2021)
This study seeks to examine the effect of the 5E learning model, as one of the constructivist learning approach models, supported by conceptual change texts and enriched with relevant guidance materials on eliminating the fifth-grade students' (n=42) misconceptions about